Composite bulletproof armor laminated structure and preparation method
By adopting a multi-stage gradient structure and dynamic response mechanism in composite bulletproof armor, the problem of existing composite armor lacking active response capabilities during dynamic impact is solved, and more efficient energy dispersion and intelligent protection performance are achieved.
Patent Information
- Application Number
- CN202510496729.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-21
- Publication Date
- 2025-06-17
- Estimated Expiration
- 2045-04-21
AI Technical Summary
The existing composite armor lacks active response capabilities when facing dynamic impacts, and the interface combination strength is insufficient, resulting in layered damage and uneven energy distribution, and insufficient protection efficiency.
The composite bulletproof armor layered structure adopts a multi-stage gradient structure, including an elastic layer, a buffer layer and a back-elastic layer, is combined with nanoborocarbide ceramics and titanium alloy microgrids, alternating layering of alumina ceramic particles and ultra-high molecular weight polyethylene fibers, shape memory polymer matrix embedded in a piezoelectric ceramic sensor array, and aramid/graphene hybrid fiber fabric and polyurethane elastomer to achieve dynamic response and energy dispersion.
Through dynamic response mechanism and multi-level gradient structure, the upgrade from passive protection to active energy guidance is achieved, which improves the armor's resistance to multiple strikes and intelligent protection performance, and significantly improves the protection efficiency.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of bulletproof armor, and particularly relates to a laminated structure of a composite bulletproof armor and a preparation method thereof. Background Art
[0002] Existing composite armors (such as ceramic / fiber laminates) rely on the static properties of materials to absorb impact energy and lack the ability to actively respond to dynamic impacts. For example, although the boron carbide composite armor improves the bulletproof performance through the combination of ceramics and titanium plates, its energy absorption efficiency is limited by the homogeneous interlayer structure, and the back bulge height reaches 25.3 mm (when the bullet speed is 500 m / s), and the protection efficiency is insufficient.
[0003] The interfacial bonding strength between ceramics and fibers is insufficient, which easily leads to delamination failure. When the ceramic composite armor is impacted, the ceramic fragments splash due to interfacial debonding, and an additional crack arrest layer (such as aramid or polyurea) is required for restraint, but this will increase the areal density (up to 46 kg / m 2 )
[0004] Traditional gradient designs are mostly single-parameter gradients (such as ceramic thickness) and do not achieve multi-level collaborative energy consumption. The interfacial adhesion force parameters of carbon fiber composite bulletproof plates are fixed, resulting in stress concentration in local areas and an enlarged damage range. Summary of the Invention
[0005] The technical problem to be solved by the present invention is to provide a laminated structure of a composite bulletproof armor and a preparation method thereof for the deficiencies in the above-mentioned existing technologies. Through a multi-level gradient structure, a dynamic response mechanism and the combination of advanced materials, the problems of passive protection, interfacial failure and energy distribution of traditional bulletproof armors are systematically solved.
[0006] The first aspect of the present invention discloses a laminated structure of a composite bulletproof armor, including a bullet-facing layer, a buffer layer and a back bullet layer. The bullet-facing layer includes a functional composite layer, and the functional composite layer sequentially includes a panel layer, an intermediate transition layer, a dynamic response layer and a back panel layer from outside to inside;
[0007] The panel layer is composed of a composite of nano-boron carbide ceramics and a titanium alloy micro-grid;
[0008] The intermediate transition layer is composed of alternating layers of alumina ceramic particles and ultra-high molecular weight polyethylene fibers. The alumina ceramic particles and the ultra-high molecular weight polyethylene fibers are connected by nano-mineral bridges. The thickness of each layer is 0.1-0.3 mm, and the particle size of the alumina ceramic particles is 50-200 μm;
[0009] The dynamic response layer is composed of a piezoelectric ceramic sensor array embedded in an SMP matrix, and the thickness of the dynamic response layer is 1-3 mm;
[0010] The backplane layer is composed of aramid / graphene hybrid fiber fabric and polyurethane elastomer through a melt impregnation process, and the thickness of the backplane layer is 5-10 mm.
[0011] For the above composite bulletproof armor laminated structure, the SMP matrix includes a shape memory polymer matrix and a continuous conductive fiber network embedded in the shape memory polymer matrix. The volume fraction of the conductive fiber is 5%-15% of the total volume of the SMP matrix, and the resistivity is 10 -3 –10 -2 Ω·m;
[0012] The arrangement path of the conductive fiber is controlled by 3D printing or die preforming to form a gradient resistance distribution, and the gradient resistance distribution satisfies R(x)=R0+kx, where x is the coordinate in the thickness direction, R0 represents the initial resistance value at the starting point of the dynamic response layer in the thickness direction, and k represents the change rate of the resistance in the thickness direction.
[0013] For the above composite bulletproof armor laminated structure, the conductive fiber is carbon fiber, nickel-titanium alloy fiber or metal-coated ceramic fiber.
[0014] For the above composite bulletproof armor laminated structure, the titanium alloy micro-grid of the panel layer is in a honeycomb structure, the honeycomb pore diameter is 0.1-0.5 mm, the wall thickness is 1 / 12 to 1 / 8 of the pore diameter, and the honeycomb pore diameter increases linearly along the thickness direction from the bullet-facing side to the back bullet-facing side.
[0015] For the above composite bulletproof armor laminated structure, the buffer layer is a shell-like laminated buffer structure, which is composed of alternately stacked alumina biomimetic sheets and aramid fiber layers. The area coverage rate of the alumina biomimetic sheets is 80%, and the layers are connected by polyurethane adhesive;
[0016] The thickness of the alumina biomimetic sheet is 0.1 mm, the length is 5-10 mm, and the width is 3-5 mm;
[0017] The single-layer thickness of the aramid fiber layer is 0.2 mm.
[0018] For the above composite bulletproof armor laminated structure, the back bullet layer uses an integrated titanium alloy grille filled with nano-SiO2-based shear thickening fluid (STF);
[0019] The porosity of the titanium alloy grille is 30%-50%, and the wall thickness is 0.5-1 mm;
[0020] The viscosity response time of the nano-SiO2-based shear thickening fluid (STF) is less than 1 ms under the condition of a shear rate of 10 6 s -1 condition.
[0021] The second aspect of the present invention discloses a method for embedding conductive fibers in the composite bulletproof armor layered structure as described above, comprising the following steps:
[0022] Step 1: Lay the conductive fibers in the shape memory polymer matrix along a preset path;
[0023] Step 2: Cure and form by hot pressing or photocuring, and control the interfacial bonding strength between the fibers and the shape memory polymer matrix > 20 MPa.
[0024] The third aspect of the present invention discloses a method for preparing a composite bulletproof armor layered structure. The preparation method of the bullet-facing layer comprises the following steps:
[0025] Step 1, faceplate layer: Prepare a titanium alloy micro-grid skeleton by selective laser melting (SLM). The honeycomb pore diameter is 0.1 - 0.5 mm, the wall thickness is 1 / 12 to 1 / 8 of the pore diameter. After filling with nano-boron carbide ceramic slurry, it is sintered by microwave. The sintering temperature is 1800 °C, the pressure is 50 MPa, and the time is 30 - 35 min to form an interpenetrating structure with a Vickers hardness > 35 GPa;
[0026] Step 2, intermediate transition layer: Alternately lay alumina ceramic particles and ultra-high molecular weight polyethylene fibers by electrostatic spraying. The particle size of the alumina ceramic particles is 50 - 200 μm. Use in-situ mineralization technology to generate nano-scale SiO2 mineral bridges. The interlayer bonding strength > 20 MPa, the hot pressing forming temperature is 120 - 130 °C, and the pressure is 5 MPa;
[0027] Step 3, dynamic response layer: Embed a lead zirconate titanate (PZT) piezoelectric ceramic sensor array in the SMP matrix by flexible circuit printing technology to form a star-shaped topological sensing network. The response time of the sensor array < 0.5 ms, and the spatial positioning accuracy is ±2 mm;
[0028] Step 4, backplate layer: Adopt a multi-axial braided resin transfer molding (RTM) process to composite aramid / graphene hybrid fiber fabric with polyurethane elastomer to form a three-dimensional interpenetrating network structure with a thickness of 5 - 10 mm.
[0029] The present invention has the following advantages compared with the prior art:
[0030] 1. The dynamic response layer is composed of a shape memory polymer (SMP) matrix embedded with a piezoelectric ceramic sensor array to form a star-shaped topological sensing network. When impacted by a projectile, the piezoelectric sensors monitor the stress distribution in real time, trigger local deformation of the SMP matrix, respond to subsequent projectile impacts, and dynamically adjust the structural stiffness to disperse the impact energy. The upgrade from "passive protection" to "active energy guidance" is achieved through dynamic response.
[0031] 2. The intermediate transition layer is composed of alternating layers of alumina ceramic particles and ultra-high molecular weight polyethylene fibers, and is connected by nano-mineral bridges. The nano-mineral bridges are generated by in-situ mineralization technology, achieving strong interfacial bonding between ceramics and fibers at a low temperature of 120 - 130 °C. The chemical bonding of the nano-mineral bridges (such as Si-O-Si bonds) enhances the interfacial durability and solves the risk of interfacial failure.
[0032] 3. The panel layer is filled with nano-boron carbide ceramics in a titanium alloy honeycomb micro-grid, forming an interpenetrating structure. The gradient design of the honeycomb pore size enables continuous transition of the shock wave impedance, dissipating energy step by step along the thickness direction. The gradient honeycomb structure prolongs the propagation path of the stress wave, and the energy absorption is increased compared to a homogeneous ceramic layer.
[0033] 4. The back panel layer is composed of a composite of aramid / graphene hybrid fiber fabric and polyurethane elastomer, forming a three-dimensional interpenetrating network structure through a melt impregnation process. Graphene enhances the interfacial toughness, and the polyurethane elastomer provides a shear thickening effect. The aramid / graphene composite back panel has improved anti-armor piercing bullet ability under the same areal density and supports multiple impact protection.
[0034] 5. The preparation method realizes the co-firing and interpenetration of the titanium alloy micro-grid and nano-boron carbide ceramics through microwave sintering, avoiding the problem of titanium alloy melting in traditional processes.
[0035] The technical solution of the present invention will be further described in detail below through examples. Detailed implementation mode
[0036] A laminated structure of a composite bulletproof armor includes a bullet-facing layer, a buffer layer, and a bullet-backing layer. The bullet-facing layer includes a functional composite layer, and the functional composite layer from outside to inside is successively a panel layer, an intermediate transition layer, a dynamic response layer, and a back panel layer;
[0037] The panel layer is composed of a composite of nano-boron carbide ceramics and titanium alloy micro-grids;
[0038] The intermediate transition layer is composed of alternating layers of alumina ceramic particles and ultra-high molecular weight polyethylene fibers. The alumina ceramic particles and ultra-high molecular weight polyethylene fibers are connected by nano-mineral bridges, and the thickness of each layer is 0.1 - 0.3 mm, and the particle size of the alumina ceramic particles is 50 - 200 μm;
[0039] The chemical synthesis path during the in-situ generation of nano-mineral bridges: "Immerse the boron carbide preform in a sodium silicate solution (concentration 1.2 mol / L, pH = 11.5) for 24 hours, then transfer it to a closed reaction kettle and introduce CO2 gas (flow rate 50 mL / min) for 6 hours, and finally heat it to 800 °C at a rate of 5 °C / min under argon protection and hold for 2 hours";
[0040] The dynamic response layer is composed of a piezoelectric ceramic sensor array embedded in an SMP matrix, and the thickness of the dynamic response layer is 1 - 3 mm;
[0041] The backplane layer is composed of aramid / graphene hybrid fiber fabric and polyurethane elastomer through a melt impregnation process, and the thickness of the backplane layer is 5 - 10 mm.
[0042] It should be noted that the piezoelectric ceramic sensors (such as lead zirconate titanate PZT) built into the dynamic response layer can monitor the stress waves generated by external impacts in real time; when the projectile impacts the armor surface, the stress waves are transmitted to this layer, and the sensors convert mechanical energy into electrical signals through the piezoelectric effect, and the response time can be controlled within 0.5 ms;
[0043] The sensor network of the piezoelectric ceramic sensors adopts a star topology structure, and each node is connected to the central processor through a flexible circuit to achieve spatial positioning of the stress distribution (with an accuracy of ±2 mm);
[0044] For the dynamic threshold determination algorithm, the central processor analyzes the stress characteristics based on a preset algorithm. When the impact intensity exceeds the preset threshold (such as 500 MPa), the response mechanism is triggered. The dynamic threshold determination algorithm needs to have anti-noise ability to filter out interference signals such as environmental vibrations, and a mature algorithm can be selected according to actual needs.
[0045] According to parameters such as the impact speed and angle, the system automatically selects the hardening mode:
[0046] Local lattice hardening: for small-caliber high-speed projectiles;
[0047] Regional gradient hardening: to deal with large-caliber armor-piercing projectiles;
[0048] Global phase transformation hardening: for explosion shock wave protection;
[0049] The phase transformation of the shape memory polymer (SMP matrix) is triggered as follows: The Joule heating effect of the SMP matrix is activated by the electrical signals generated by the sensors, so that the material temperature rises above the glass transition temperature within 1 ms, triggering molecular chain rearrangement and modulus jump (from 1 GPa to 5 GPa).
[0050] The adjustment mechanism of the dynamic stiffness is as follows: After phase transformation, the SMP forms an interlocking lattice structure, and its storage modulus increases exponentially with the increase of the strain rate, realizing the strain rate strengthening effect of "the stronger the stronger". Experimental data shows that at a strain rate of 1000 s -1 The energy absorption efficiency of the material is increased by 40%.
[0051] The hardening area dissipates the impact energy in the following ways: grain boundary slip (about 35% proportion), molecular chain fracture (about 25% proportion), and piezoelectric ceramic dielectric loss (about 20% proportion).
[0052] After the impact ends, the SMP matrix returns to its original state through the entropy elasticity of molecular chains during the cooling process. Meanwhile, the piezoelectric element supplies power in reverse to accelerate the repair process. After testing, this layer can withstand more than 3 impacts of B7 level and still maintain 90% of its initial performance.
[0053] It should be noted that the dynamic response layer mimics the stress response mechanism of the pain-sensing nerves in the human skin, integrating the coupling effects of mechanics, electricity, and thermotics. Compared with traditional active protection systems, the energy consumption is reduced by 70%. The working principle has been verified by Ansys Workbench dynamic simulation. In the scenario of a 12.7mm armor-piercing projectile impact, the dynamic response layer improves the overall anti-penetration ability of the armor.
[0054] The ability to resist 12.7mm armor-piercing projectiles reaches the B7 level of protection standard (the measured areal density ≤ 35 kg / m 2 , 25% lower than that of traditional armor), and the dynamic response layer improves the secondary impact protection efficiency by 30%.
[0055] Furthermore, it should be noted that the high hardness of the panel layer (Vickers hardness > 35 GPa) can effectively break the projectile, and the gradient pore size design of the titanium alloy micro-grid enhances the ability to resist multiple strikes. The alternating layering and mineral bridging of the intermediate transition layer significantly improve the energy absorption efficiency and inhibit crack propagation. The dynamic response layer realizes real-time damage monitoring and active stiffness adjustment, improving the intelligent protection ability of the armor. The three-dimensional network structure of the back panel layer has both high toughness and lightweight (areal density < 50 kg / m 2 ), meeting the high-strength protection requirements.
[0056] Piezoelectric signal triggering mechanism, description:
[0057] The electrothermal conversion link between the piezoelectric ceramic (PZT-5H) and the shape memory polymer: When the impact load > 500 N, the piezoelectric unit generates a voltage ≥ 15 V, which is input into the nickel-chromium alloy wire (diameter 0.1 mm, resistivity 1.1 Ω / m) implanted in the SMP through a full-bridge rectifier circuit (diode model 1N4007). Through the Joule effect, the material temperature rises to the phase change critical point;
[0058] Multi-stage response coordination description:
[0059] Gradient trigger threshold: The surface conductive fiber is activated when the strain rate > 10 3 s -1 The middle-layer piezoelectric unit is triggered when the pressure > 300 kPa, and the bottom-layer SMP layer starts to undergo a phase change after a 2 ms delay.
[0060] Failure protection mechanism:
[0061] When the main power supply is interrupted, it is maintained by a 3.7V lithium thionyl chloride battery (model ER14505M) for at least 3 complete response cycles, and the output voltage fluctuation ≤ ±5%;
[0062] In this embodiment, the SMP matrix includes a shape memory polymer matrix and a continuous conductive fiber network embedded in the shape memory polymer matrix, and the conductive fiber is selected as a high-performance conductive fiber; the volume fraction of the high-performance conductive fiber is 5%-15% of the total volume of the SMP matrix, and the resistivity is 10 -3 –10 -2 Ω·m;
[0063] The arrangement path of the conductive fiber is controlled by 3D printing or mold preforming to form a gradient resistance distribution, and the gradient resistance distribution satisfies R(x)=R0+kx, where x is the coordinate in the thickness direction, R0 represents the initial resistance value at the starting point of the dynamic response layer in the thickness direction, and k represents the change rate of the resistance in the thickness direction.
[0064] It should be noted that the conductive fiber network realizes the gradient resistance distribution (R(x)=R0+kx) through 3D printing or mold preforming, with a volume fraction of 5%-15% and a resistivity of 10 -3 –10 -2 Ω·m. The carbon nanotube / polypyrrole composite fiber is prepared by the electrospinning process, and the density linearly increases from 0.1 g / cm 3 (R0 = 10Ω) to 0.3 g / cm 3 (Rmax = 50Ω), and the measured resistance distribution is R(x)=10+0.8x (R 2 = 0.992), and the error ≤ ±10%.
[0065] Adopt hot pressing (120-130°C, 5 MPa) or ultraviolet curing (wavelength 365 nm), the interfacial bonding strength > 20 MPa to ensure the electro-mechanical coupling stability; the gradient resistance distribution optimizes the current path, enhances the shape recovery efficiency of the SMP matrix, and realizes the dynamic stiffness adjustment; the shape recovery efficiency of the SMP matrix is increased by 30%, and the impact energy dissipation rate > 70%;
[0066] The synergistic effect of the conductive network and the SMP matrix can quickly dissipate the impact energy and reduce the deformation of the back elastic layer (BFS < 35 mm).
[0067] The realization of the conductive fiber gradient is described as follows: a seven-layer gradient structure is adopted, the volume fraction of carbon fiber linearly increases from 5% to 15%, the thickness of each layer is 0.3 mm, and the fiber orientation is staggered at 45° with the impact direction; the four-probe method (equipment model Keithley 2450) is used to measure the resistance value every 0.1 mm along the thickness direction, and the fitting curve R 2 > 0.98 is regarded as qualified;
[0068] In this embodiment, the conductive fiber is carbon fiber, nickel-titanium alloy fiber and / or metal-coated ceramic fiber.
[0069] It should be noted that the carbon fiber is of high modulus T800 grade, with a thermal conductivity > 30 W / m·K to avoid local melting; the surface is nitrided to improve the interfacial bonding strength with the SMP matrix;
[0070] If nickel-titanium alloy fiber is used, the nickel-titanium alloy fiber needs to be prepared by a cold drawing process, with a diameter ≤ 50 μm, so that it has both shape memory effect and conductivity;
[0071] If metal-coated ceramic fiber (such as silver-coated Al2O3 fiber) is used, surface metallization needs to be achieved through electroless plating process to make its resistivity adjustable, and the resistivity can be adjusted to 10 -4 Ω·m.
[0072] The high thermal conductivity (> 30 W / m·K) of the carbon fiber can quickly disperse the impact heat effect and avoid local melting. The phase change characteristics of the nickel-titanium alloy fiber endow the dynamic response layer with self-healing ability.
[0073] In this embodiment, the titanium alloy micro-grid of the panel layer is in a honeycomb structure, the honeycomb pore diameter is 0.1 - 0.5 mm, the wall thickness is 1 / 12 to 1 / 8 of the pore diameter, and the honeycomb pore diameter increases linearly along the thickness direction from the bullet-facing surface to the back bullet-facing surface.
[0074] It should be noted that the honeycomb pore diameter increases linearly from the bullet-facing surface (0.1 mm) to the back bullet-facing surface (0.5 mm), and the wall thickness increases synchronously. Precise structure control is achieved by SLM layer-by-layer printing, and the SLM layer-by-layer printing control accuracy is ±0.1 mm; after filling with nano B4C slurry and microwave sintering, a ceramic-metal interpenetrating network is formed, with a density greater than 99.5%;
[0075] The gradient pore diameter design disperses the stress wave propagation path and reduces the penetration speed of the projectile (the projectile speed attenuation rate > 30%); the interpenetrating structure improves the flexural strength (> 560 MPa) and fracture toughness (> 5.7 MPa·m 1 / 2 ).
[0076] In this embodiment, the buffer layer is a shell-like buffer structure, which is composed of alternately stacked alumina biomimetic sheets and aramid fiber layers. The area coverage rate of the alumina biomimetic sheets is 80%, and the layers are connected by polyurethane adhesives;
[0077] The thickness of the alumina biomimetic sheet is 0.1 mm, the length is 5 - 10 mm, and the width is 3 - 5 mm;
[0078] The single-layer thickness of the aramid fiber layer is 0.2 mm.
[0079] It should be noted that the alumina bionic sheet (0.1 mm thick, 5 - 10 mm long) is formed by laser cutting, and micro-grooves are etched on the surface to enhance the mechanical interlock with aramid fibers; the polyurethane adhesive adopts a two-component system (A:B = 3:1), and after curing, the modulus > 1 GPa and the interlaminar shear strength > 15 MPa;
[0080] The "brick - mud" structure imitating the shell improves the fracture toughness through mechanisms such as crack deflection and fiber bridging (3 times higher than that of homogeneous ceramics); the plastic deformation of the aramid fiber layer (single layer 0.2 mm) can absorb the remaining energy and inhibit the cracking of the back panel layer.
[0081] In this embodiment, the back bulletproof layer adopts an integral titanium alloy grid filled with nano - SiO₂ - based shear thickening fluid (STF);
[0082] The porosity of the titanium alloy grid is 30% - 50%, and the wall thickness is 0.5 - 1 mm;
[0083] The viscosity response time of the nano - SiO₂ - based shear thickening fluid (STF) is less than 1 ms under the shear rate of 10 6 s -1 conditions.
[0084] It should be noted that the porosity of the titanium alloy grid is 30% - 50%, and the wall thickness is 0.5 - 1 mm. It is connected to the back panel by laser welding (weld strength ≥ 300 MPa); the nano - SiO₂ - based STF is prepared by dispersing SiO₂ with a particle size of 20 nm in polyethylene glycol (PEG), and the viscosity response time is < 1 ms under the shear rate of 10 6 s -1 ; the shear thickening effect of STF can instantaneously harden and dissipate the impact energy (energy absorption rate > 70%); the pore design of the titanium alloy grid takes into account both lightweight (density 2.5 g / cm 3 ) and anti - deformation ability.
[0085] Preparation of shear thickening liquid: Fumed silica with a particle size of 15 ± 3 nm (specific surface area 200 ± 10 m 2 / g) is used, and 1.5 wt% of polyethylene oxide (molecular weight 2 million) is added as a dispersant. After ultrasonic treatment (40 kHz, 800 W) for 30 minutes, it is left to stand and defoam for 48 hours.
[0086] Another embodiment of the present invention also discloses a method for embedding conductive fibers in a composite bulletproof armor layered structure, including the following steps:
[0087] Step 1: Lay the conductive fibers in the shape - memory polymer matrix according to a preset path;
[0088] Step 2: Carry out curing and forming by hot pressing or light curing, and control the interfacial bonding strength between the fiber and the shape memory polymer matrix > 20 MPa.
[0089] It should be noted that the embedding of conductive fibers is carried out by hot pressing curing (temperature 120 - 130 °C, pressure 5 MPa) or ultraviolet light curing (wavelength 365 nm) to ensure that the fiber - matrix interfacial bonding strength > 20 MPa;
[0090] Another embodiment of the present invention also discloses a preparation method of a composite bulletproof armor laminated structure. The preparation method of the bullet - facing layer includes the following steps:
[0091] Step 1, panel layer: Prepare a titanium alloy micro - grid skeleton by selective laser melting (SLM). The honeycomb pore diameter is 0.1 - 0.5 mm, the wall thickness is 1 / 12 to 1 / 8 of the pore diameter. After filling with nano - boron carbide ceramic slurry, it is sintered by microwave. The sintering temperature is 1800 °C, the pressure is 50 MPa, and the time is 30 - 35 min to form an interpenetrating structure with a Vickers hardness > 35 GPa; the protective gas for microwave sintering is argon, and the oxygen content ≤ 10 ppm;
[0092] The content of β - phase in the titanium alloy matrix ≥ 85%, the grain size ≤ 50 μm, and the oxygen content ≤ 0.15 wt%;
[0093] The titanium alloy micro - grid is prepared by selective laser melting (SLM) process. The honeycomb pore diameter gradually increases from 0.1 mm on the bullet - facing surface to 0.5 mm on the back - bullet surface, and the wall thickness is 1 / 12 to 1 / 8 of the pore diameter. After filling with nano - boron carbide ceramic slurry, it is sintered by microwave (1800 °C, 50 MPa) to form an interpenetrating structure with a relative density > 99.5%.
[0094] The Vickers hardness > 35 GPa, the flexural strength > 560 MPa, the bullet velocity attenuation rate > 30%, realizing lightweight (areal density < 50 kg / m 2 ) and high anti - penetration performance;
[0095] When the microwave sintering process is carried out, in order to prevent melting, a 2.45 GHz microwave source is used, and the power density is controlled at 8 W / cm 3 , combined with forced argon cooling (flow rate 20 L / min), so that the surface temperature of the material ≤ 1650 °C while the core reaches 1750 ± 20 °C; a microwave gradient sintering process is adopted. The core is protected by a ZrO2 thermal insulation coating, and the temperature is controlled at 1750 ± 20 °C (meeting the sintering of Al2O3 ceramics), and the surface temperature is controlled ≤ 1650 °C by Ar gas cooling (lower than the melting point of titanium alloy); the micro - hardness of the titanium alloy after sintering ≥ 350 HV;
[0096]
[0097] During sintering quality inspection, through XRD semi-quantitative analysis (using a Rigaku SmartLab device), the content of β-Ti phase is required to be ≥85%, and the porosity detection (by the Archimedes method) is ≤3%;
[0098] For microwave sintering temperature, a deviation of ±25°C is allowed, the fluctuation of SLM laser power is ≤±3%, and the error of the laying angle of conductive fibers is ≤±5°;
[0099] During SLM forming, Ti-6Al-4V powder (particle size 15 - 45μm) is used, the laser power is 250W, the scanning speed is 800mm / s, the layer thickness is 30μm, and the honeycomb wall thickness is designed to be 1 / 10 of the pore diameter (for example, a 0.1mm pore diameter corresponds to a 10μm wall thickness); a grid support is set at the bottom of each layer of the honeycomb structure, the line width is 80μm, the spacing is 1.2mm, the support material is the same-quality titanium alloy, and it is removed by pickling (HNO3:HF = 3:1 solution, soaking time ≤30s).
[0100] Step 2, Intermediate transition layer: Alumina ceramic particles and ultra-high molecular weight polyethylene fibers are alternately laid by electrostatic spraying. The particle size of the alumina ceramic particles is 50 - 200μm. Nano-scale SiO2 mineral bridges are generated by in-situ mineralization technology. The interlayer bonding strength is >20MPa, the hot pressing forming temperature is 120 - 130°C, and the pressure is 5MPa;
[0101] Alumina ceramic particles (particle size 50 - 200μm) and ultra-high molecular weight polyethylene fibers (UHMWPE) are alternately laid by electrostatic spraying, with each layer having a thickness of 0.2mm. They are connected by nano-SiO2 mineral bridges, and the hot pressing temperature is 120 - 130°C and the pressure is 5MPa;
[0102] The interlayer bonding strength is >20MPa, the energy absorption efficiency is increased by 40%, and the crack propagation is inhibited.
[0103] Step 3, Dynamic response layer: The lead zirconate titanate (PZT) piezoelectric ceramic sensor array is embedded in the SMP matrix by using flexible circuit printing technology to form a star-shaped topological sensing network. The response time of the sensor array is <0.5ms, and the spatial positioning accuracy is ±2mm;
[0104] The lead zirconate titanate (PZT) piezoelectric ceramic sensor array is embedded in the SMP matrix by flexible circuit printing to form a star-shaped topological network. The response time is <0.5ms, and the spatial positioning accuracy is ±2mm; after the sensor detects an impact signal, the signal processing unit triggers a response within 0.5ms, and the conductive fibers heat the shape memory polymer matrix through a high-frequency pulsed current (frequency ≥10kHz, pulse width 50μs) to complete the phase change within 5ms, realizing dynamic stiffness adjustment.
[0105] Real-time monitor the impact point and trigger the adjustment of the SMP matrix stiffness, with the backplane depression (BFS) < 35 mm.
[0106] Step 4, backplane layer: Adopt the resin transfer molding (RTM) process of multi-axial weaving to composite the aramid / graphene hybrid fiber fabric with the polyurethane elastomer to form a three-dimensional interpenetrating network structure, with a thickness of 5 - 10 mm.
[0107] The aramid / graphene hybrid fiber fabric is composite with the polyurethane elastomer by the multi-axial RTM process to form a three-dimensional interpenetrating network, with a thickness of 5 - 10 mm, an interlaminar shear strength > 25 MPa; a fracture toughness > 5.7 MPa·m¹ / ², and the delamination resistance ability is improved by 50%.
[0108] It should be noted that the SLM and microwave sintering processes achieve high-precision forming of complex structures (dimension error ±0.1 mm); the three-dimensional weaving of the RTM process enhances the delamination resistance ability of the backplane layer (interlaminar shear strength > 25 MPa).
[0109] It should be noted that through the collaborative design of multi-level materials and structures, the present invention achieves the following technical effects:
[0110] Lightweight: Areal density < 50 kg / m 2 , with a weight reduction of 50% compared to traditional steel armor;
[0111] Multi-shot resistance ability: The gradient honeycomb structure and the shell-like layer inhibit crack propagation and can withstand the strike of 6 rounds of 12.7 mm armor-piercing bullets;
[0112] Intelligent protection: The dynamic response layer realizes real-time damage monitoring and active stiffness adjustment.
[0113] Dynamic performance test of the present invention:
[0114] 1. High-speed impact test parameters:
[0115] Adopt a 14.5 mm armor-piercing bullet (bullet core hardness 62 HRC), initial velocity 980 ± 15 m / s, and use a laser velocimeter (Polytec PDV - 100) and a dynamic strain gauge (sampling rate 1 MHz) to synchronously collect data;
[0116] 2. Phase change speed verification:
[0117] Record the temperature field change through a high-speed infrared thermal imager (FLIR X8580, frame rate 10 kHz), and require that the time from power-on to complete phase change ≤ 25 ms;
[0118] 3. Environmental aging test:
[0119] Conduct 10 temperature cycles (-55°C to 125°C) according to GJB150.9A-2009, and the energy absorption rate attenuation after testing shall be ≤8%; after 1000 hours of damp heat test (40°C, 95%RH), the resistance change rate shall be ≤5%;
[0120] 4. Anti-ballistic test data of composite armor (refer to GJB 4300A-2022):
[0121]
[0122] The above are only the preferred embodiments of the present invention, and do not impose any limitations on the present invention. Any simple modifications, changes, and equivalent structural changes made to the above embodiments based on the technical essence of the present invention still fall within the protection scope of the technical solution of the present invention.
Claims
1. A composite bulletproof armor layer structure, comprising a bullet-facing layer, a buffer layer and a bullet-proof layer, characterized in that: The anti-bullet layer includes a functional composite layer, which is composed of a panel layer, an intermediate transition layer, a dynamic response layer and a back panel layer from the outside to the inside. The panel layer is composited with nano boron carbide ceramics and titanium alloy microgrids; The intermediate transition layer is composed of alternating layers of alumina ceramic particles and ultra-high molecular weight polyethylene fibers, the alumina ceramic particles and the ultra-high molecular weight polyethylene fibers are connected by nano mineral bridges, each layer has a thickness of 0.1-0.3 mm, and the particle size of the alumina ceramic particles is 50-200 μm; The dynamic response layer is composed of a piezoelectric ceramic sensor array embedded in an SMP matrix, and the thickness of the dynamic response layer is 1-3 mm; The back plate layer is formed by compounding aramid / graphene hybrid fiber fabric with polyurethane elastomer through a melt impregnation process, and the thickness of the back plate layer is 5-10 mm.
2. The composite bulletproof armor layered structure according to claim 1, characterized in that: The SMP matrix includes a shape memory polymer matrix and a continuous conductive fiber network embedded in the shape memory polymer matrix, wherein the volume fraction of the conductive fiber is 5%-15% of the total volume of the SMP matrix and the resistivity is 10 -3 –10 -2 Ω·m; The arrangement path of the conductive fibers is controlled by 3D printing or mold preforming to form a gradient resistance distribution, and the gradient resistance distribution satisfies R(x)=R0+kx, where x is the thickness direction coordinate, R0 represents the initial resistance value of the dynamic response layer at the starting point in the thickness direction, and k represents the rate of change of resistance in the thickness direction.
3. The composite bulletproof armor layered structure according to claim 2, characterized in that: The conductive fiber is carbon fiber, nickel-titanium alloy fiber or metal-plated ceramic fiber.
4. The composite bulletproof armor layered structure according to claim 1, characterized in that: The titanium alloy microgrid of the panel layer is a honeycomb structure with a honeycomb aperture of 0.1-0.5 mm and a wall thickness of 1 / 12 to 1 / 8 of the aperture. The honeycomb aperture increases linearly along the thickness direction from the projectile-facing surface to the anti-projectile surface.
5. The composite bulletproof armor layered structure according to claim 1, characterized in that: The buffer layer is a shell-like layered buffer structure, which is composed of alternately stacked alumina bionic sheets and aramid fiber layers, with the area coverage of the alumina bionic sheets being 80%, and the layers being connected by a polyurethane adhesive; The alumina bionic sheet has a thickness of 0.1 mm, a length of 5-10 mm, and a width of 3-5 mm; The thickness of a single layer of the aramid fiber layer is 0.2 mm.
6. The composite bulletproof armor layered structure according to claim 1, characterized in that: The back-spring layer adopts an integrated titanium alloy grid filled with nano-SiO2-based shear thickening fluid; The porosity of the titanium alloy grid is 30%-50%, and the wall thickness is 0.5-1mm; The viscosity response time of the nano-SiO2 based shear thickening fluid is 10 6 s -1 Under normal conditions, it is less than 1ms.
7. A method for embedding conductive fibers into a composite bulletproof armor layer structure as claimed in claim 2, characterized in that: The following steps are involved: Step 1: Laying the conductive fibers in a shape memory polymer matrix along a preset path; Step 2: Use hot pressing or light curing to perform curing and molding, and control the interface bonding strength between the fiber and the shape memory polymer matrix to be greater than 20 MPa.
8. A method for preparing a composite bulletproof armor layered structure according to any one of claims 1 to 6, characterized in that: The preparation method of the anti-bullet layer comprises the following steps: Step 1, panel layer: prepare titanium alloy micro-grid skeleton by laser selective melting, the honeycomb aperture is 0.1-0.5mm, the wall thickness is 1 / 12 to 1 / 8 of the aperture, fill with nano boron carbide ceramic slurry and then sinter by microwave, the sintering temperature is 1800℃, the pressure is 50MPa, the time is 30-35min, and an interpenetrating structure is formed, and the Vickers hardness is greater than 35GPa; Step 2, intermediate transition layer: Alternately lay alumina ceramic particles and ultra-high molecular weight polyethylene fibers by electrostatic spraying, the particle size of alumina ceramic particles is 50-200μm, and nano-scale SiO2 mineral bridges are generated by in-situ mineralization technology, the interlayer bonding strength is greater than 20MPa, the hot pressing temperature is 120-130℃, and the pressure is 5MPa; Step 3, dynamic response layer: the lead zirconate titanate piezoelectric ceramic sensor array is embedded in the SMP substrate using flexible circuit printing technology to form a star topology sensor network. The sensor array response time is less than 0.5ms and the spatial positioning accuracy is ±2mm. Step 4, backplane layer: A multi-axially woven resin transfer molding process is used to compound the aramid / graphene hybrid fiber fabric with the polyurethane elastomer to form a three-dimensional interpenetrating network structure with a thickness of 5-10 mm.
Citation Information
Patent Citations
Lightweight functionally graded composite bulletproof armor plate and preparation method thereof
CN112140654A
Combined type bulletproof plate and preparation method thereof
CN115265278A